Manipulating Terahertz Plasmonic Vortex Based on Geometric and Dynamic Phase. Issue 3 (6th December 2018) - Zang, XiaoFei; Zhu, YiMing; Mao, ChenXi; Xu, WeiWei; Ding, HongZhen; Xie, JingYa; Cheng, QingQing; Chen, Lin; Peng, Yan; Hu, Qing; Gu, Min; Zhuang, SongLin
Abstract: Electromagnetic waves carrying orbital angular momentum (OAM), namely, vortex beams, have a plethora of applications ranging from rotating microparticles to high‐capacity data transmissions, and it is a continuing trend in manipulating OAM with higher degrees of freedom. Here, an approach to control terahertz (THz) near‐field plasmonic vortex based on geometric and dynamic phase is proposed and experimentally demonstrated. By locally tailoring the orientation angle (geometric phase) and radial position (dynamic phase) of aperture arrays embedded in an ultrathin gold film, the excited surface waves can be flexibly engineered to form both spin‐independent and spin‐dependent THz plasmonic vortex field distributions, resulting in multi‐degree of freedom for controlling OAM of THz surface plasmon polaritons (SPPs). Arbitrary OAM values of THz plasmonic vortex and coherent superposition between two OAM states are investigated based on near‐field scanning terahertz microscopy (NSTM) system. The proposed approach provides unprecedented freedom to modulate THz near‐field plasmonic vortex, which will have potential applications in THz communications and quantum information processing. Abstract : A novel ultrathin platform is proposed and experimentally demonstrated to realize the manipulation of terahertz (THz) near‐field orbital angular momentum (OAM). By locally tailoring the orientation angle and radial position of aperture arrays in a gold film, the surface plasmon polaritons (SPPs) can be flexibly engineered to form both spin‐independent and spin‐dependent THz plasmonic vortex field, resulting in multi‐degree of freedom for controlling OAM of THz SPPs.